Observed Ground Pressure Acting on the Lining of a Large-Diameter Shield Tunnel in Sandy Stratum under High Water Pressure. (9th March 2020) - Li, Xue; Zhou, Shunhua; Di, Honggui
Abstract : Accurately evaluating the ground pressure on the tunnel lining greatly helps the structure design of a tunnel. In this study, the earth pressure and water pressure on the tunnel lining of four cross sections of a metro tunnel were measured and analyzed and then compared with the theoretical values. Results show that the values and distribution of observed ground pressure acting on the lining are different for different overburden depths. The water pressure measured on-site is approximately equal to the theoretical hydrostatic pressure. The water pressure acting on the shield tunnel lining does not fluctuate with the shield tunnel excavation. The maximum ground pressure was measured in the process of backfill grouting, and the maximum values are approximately larger than 30% of the stable value of the measured pressure. For a shield tunnel under a river with deep water, the water pressure on the lining is dominant and the observed total ground pressure is nearly equal to the water pressure. The findings presented in this paper can provide a reference for the structure design of similar tunnel projects.